Associations between maternal obesity, gestational cytokine levels and child obesity in the NEST cohort. Issue 7 (30th December 2020) - Maguire, Rachel L.; House, John S.; Lloyd, Dillon T.; Skinner, Harlyn G.; Allen, Terrence K.; Raffi, Asifa Mohamed; Skaar, David A.; Park, Sarah S.; McCullough, Lauren E.; Kollins, Scott H.; Bilbo, Staci D.; Collier, David N.; et al.
Summary: Background: Although maternal systemic inflammation is hypothesized to link maternal pre‐pregnancy obesity to offspring metabolic dysfunction, patient empirical data are limited. Objectives: In this study, we hypothesized that pre‐pregnancy obesity alters systemic chemo/cytokines concentrations in pregnancy, and this alteration contributes to obesity in children. Methods: In a multi‐ethnic cohort of 361 mother‐child pairs, we measured prenatal concentrations of plasma TNF‐α, IL‐6, IL‐8, IL‐1β, IL‐4, IFN‐γ, IL‐12 p70 subunit, and IL‐17A using a multiplex ELISA and examined associations of pre‐pregnancy obesity on maternal chemo/cytokine levels, and associations of these cytokine levels with offspring body mass index z score (BMI‐z) at age 2–6 years using linear regression. Results: After adjusting for maternal smoking, ethnicity, age, and education, pre‐pregnancy obesity was associated with increased concentrations of TNF‐α ( P = .026) and IFN‐γ ( P = .06). While we found no evidence for associations between TNF‐α concentrations and offspring BMI‐z, increased IFN‐γ concentrations were associated with decreased BMI‐z ( P = .0002), primarily in Whites ( P = .0011). In addition, increased maternal IL‐17A concentrations were associated with increased BMI‐z in offspring ( P = .0005) with stronger associations in African Americans ( P = .0042) than Whites ( P = .24). Conclusions: Data from this study are consistent with maternal obesity‐related inflammation during pregnancy, increasing the risk of childhood obesity in an ethnic‐specific manner.